The anterior-posterior gradient of the fusiform gyrus modulates the transition between mnemonic and perceptual features during reminiscences - Motong Yuan; Yanyan Li; Jing Wang; Yufei Cai; Wenya Yang; Mengyang Wang; Bo Zhang; Hongwei Sun; Guoming Luan; Georg Northoff; Liang Wang (Nature Communications)
Abstract Our cognition can be oriented either towards the external environment, as in perception, or towards our own self and its memories. However, the perception-memory continuum underlying the construction of memories remains unclear. Addressing this gap in our knowledge is the goal of our study; for that we uniquely investigate a rare mental phenomenon, namely internally- and externally-oriented reminiscences as manifest in memories and experiential hallucinations. To probe the causality of precisely located areas in eliciting and structuring such perceptual-mnemonic interactions, we studied a large sample of 335 patients with electrodes implanted across nearly the entire cortical surface, combining intracranial electrical stimulation (iES) and electrophysiological causal connectivity. We demonstrate that the likelihood of internally-oriented reminiscences was significantly higher during stimulation of the anterior fusiform gyrus. Conversely, externally-oriented hallucinations were far more likely to occur upon stimulation of the posterior fusiform gyrus. The probability of connections from regions outside the fusiform gyrus that displayed internally-oriented reminiscences to the fusiform gyrus decreased along the anterior-posterior axis. This suggests that an anterior-posterior gradient within the fusiform gyrus mediates an analogous external-internal perceptual-mnemonic continuum.